'An elegant surpassing of the truth': Interrogating authenticity, authorship, and the production of value in The Story of My Teeth. Issue 2 (1st June 2022) - Brown, Katie
Abstract : Resulting from a collaboration with workers at the Jumex factory and responding to an exhibition at the Jumex art gallery, La historia de mis dientes [ The Story of my Teeth ] by Valeria Luiselli interrogates the ways in which stories can be used to market objects, places, and people and the values attached to the names of authors and artists. Attention to the changes made to the text in the English translation highlights these central concerns, while analysis of the figure of Voragine, who writes the 'dental autobiography' of the novel's protagonist, Highway, reveals a parody of the testimonio, a genre that derives its value primarily from its supposed authenticity.